Right atrial tachycardia with 2:1 intra-atrial conduction - Masayoshi Kofune, MD, PhD; Ichiro Watanabe, MD, PhD; Yasuo Okumura, MD, PhD (Journal of Arrhythmia, 2015)
In a case of atrial tachycardia (AT) originating from the inferolateral right atrium, cycle length (CL) alternans was observed. Conduction at the longer CL was to the high right atrium (HRA), His bundle electrogram region (HBE), and coronary sinus (CS). Conduction at the shorter CL was to the HRA, with that to the HBE and CS blocked.